Measurements of the doses of eye lens for the workers of Fukushima Daiichi Nuclear Power Plant. (November 2020) - Yokoyama, Sumi; Ezaki, Iwao; Tatsuzaki, Hideo; Tachiki, Shuichi; Hirao, Shigekazu; Aoki, Katsunori; Tanimura, Yoshihiko; Hoshi, Katsuya; Yoshitomi, Hiroshi; Tsujimura, Norio
Abstract: In Japan, the possibility to change the current dose limit of the lens of the eye for the radiation workers working in the planned exposure situation (normal controlled situations) to a new ICRP dose limit was discussed. It was further discussed how to appropriately monitor and manage the equivalent dose of the eye lenses for these workers exposed to radiation at their workplaces, such as nuclear and medical facilities. Among the workers exposed to a high-dose radiation at the water storage flange tank deconstructed 90 Sr/ 90 Y dominant areas and the nuclear reactor buildings (high dose gamma-ray) of the Fukushima Daiichi Nuclear Power Plant (1F-NPP), H p (10), H p (3), and H p (0.07) at the head and the chest (or the upper arm) were estimated by passive personal dosimeters using thermoluminescence dosimeters (TLDs) and radio photoluminescence glass dosimeters (RPLGDs). The relationship between H p (10), H p (3), and H p (0.07) along with the effects of the sites of wearing dosimeters on the head inside a full-face mask and the chest (or upper arm) were discussed. Highlights: Radiation exposure of Fukushima Daiichi Nuclear Power Plant workers was evaluated. Occupational radiation exposure is high owing to decommissioning post accidents. They work in the 90 Sr/ 90 Y beta-ray or gamma-ray exposure-dominant fields. H p (3), H p (10), and H p (0.07) were measured by passive personal dosimeters.